Pengaruh Flexible Working Space dan Flexible Working Time terhadap Kinerja Tim melalui Kerja Sama Tim pada Perusahaan Pengembangan Perangkat Lunak di Indonesia - Benny Susanto; Wilson Bangun (SAFE-Network, 2023)
The terms flexible working space and flexible working time have become popular recently after the occurrence of the COVID-19 pandemic and the emergence of technology startup companies that adopt a new work model where work arrangements are flexible in terms of both place (Flexible Working Space) and time (Flexible Working Time). However, there are concerns from management regarding the decline in employee performance if these work arrangements are adopted, due to a decrease in team collaboration effectiveness caused by separate workspaces (flexispace). This article aims to examine the impact of Flexible Working Space and Flexible Working Time on team performance through team collaboration in software development companies in Indonesia and contribute by providing findings on the impact of flexible work arrangements in terms of place and time that can be useful for companies that have or will implement flexible work systems and require information regarding the impact of such work arrangements. The population consists of team leads/managers from across Indonesia who are part of various software developer communities. Data was collected using convenience sampling technique through a questionnaire. The number of samples used was 97. The data analysis method used is PLS-SEM with the assistance of SmartPLS software.